Peningkatan Hasil Belajar Menyanyi Solo Menggunakan Media Pembelajaran Smart Apps Creator (SAC) - Sriningsih, Endang (Jurnal Didaktika Pendidikan Dasar, 2024)
Online and offline learning during the Covid-19 pandemic requires teachers to ensure that participants remain enthusiastic and active in learning. This research aims to improve student learning outcomes in solo singing material by utilizing interactive learning media in the form of Smart Apps Creator (SAC). This Classroom Action Research was carried out at SMPN 4 Mataram in class IX, Odd Semester of the 2020/2021 Academic Year. Data from student learning outcomes regarding knowledge and skills aspects in cycles I, II and III are analyzed quantitatively and followed up in each learning cycle.  The research results show that the use of SAC learning media can improve learning outcomes.  The increase in student learning outcomes in the knowledge aspect from cycle I to cycle II increased by 20.6 points and from cycle II to cycle III increased by 12.4 points.  The skills aspect from cycle I to cycle II increased by 19 points and from cycle II to cycle III increased by 17 points.  So, students can use SAC learning media and students' learning outcomes in solo singing material aspects of knowledge and skills increase.